2020
DOI: 10.12688/f1000research.25076.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis of selected phytochemicals on two SARS-CoV-2 targets

Abstract: Background: The coronavirus spike (S) glycoprotein and M protease are two key targets that have been identified for vaccines and drug development against COVID-19. Methods: Virtual screening of some compounds of plant origin that have shown antiviral activities were carried out on the two targets, the M protease (PDB ID 6LU7) and S glycoprotein (PDB ID 6VSB), by docking with PyRx software. The binding affinities were compared with other compounds and drugs already identified as potential ligands for the M prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…ADMET analysis ADME/T (Absorption, distribution, Metabolism, Excretion, and Toxicity) analysis was performed using Drulito software (www.niper.gov.in/pi_dev_tools/DruLiToWeb /DruLiTo_index.html) to study the pharmacokinetics pro le of the identi ed compounds for potential drug development [47,48]. The compounds were ranked based on two lters: the Lipinski rule and the ability to pass through the blood brain barrier (BBB).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…ADMET analysis ADME/T (Absorption, distribution, Metabolism, Excretion, and Toxicity) analysis was performed using Drulito software (www.niper.gov.in/pi_dev_tools/DruLiToWeb /DruLiTo_index.html) to study the pharmacokinetics pro le of the identi ed compounds for potential drug development [47,48]. The compounds were ranked based on two lters: the Lipinski rule and the ability to pass through the blood brain barrier (BBB).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Pioglitazone was also included in the list of candidate compounds for SARS-CoV-2 screened by an in silico method [19]. Quercetin was reported to inhibit the cell entry of SARS-CoV-2 [20], and was also included in the list of candidate compounds for SARS-CoV-2 screened by an in silico method [21]. Fenretinide was also included in the drugs identified as effective compounds in the "Drug perturbations from GEO up" category as described above.…”
Section: F Drug Discoverymentioning
confidence: 99%
“…Finally, we compared the drugs screened out using our approach from the "Drug perturbations from GEO up/down" lists with those screened from two in silico drug discovery studies [19], [21] 1) Comparison with Wu et al [19]: We found multiple hits, which are summarized in Table X. The main drugs identified included doxycycline, ascorbic acid, isotretinoin, pioglitazone, cortisone, and tibolone.…”
Section: G Comparison With In Silico Drug Discoverymentioning
confidence: 99%
See 2 more Smart Citations